Russian peasants go to court : legal culture in the countryside, 1905-1917 - Burbank, Jane (Indiana University Press, 2004)
A study of the legal culture of Russian peasants in the closing years of the Russian Empire Russian Peasants. Jane Burbank's study of court records reveals engaged rural citizens who valued order in their communities and made use of state courts to seek justice and to enforce and protect order.